Characteristics of Tris(chloropropyl)phosphate (TCPP) emission from upholstered furniture in offices and consequence on indoor air quality. (1st July 2022) - Plaisance, Herve; Raffy, Gaëlle; Le Bot, Barbara; Bossanne, Emilie; Rawas, Clemence; Cardin, Pierre; Desauziers, Valerie
Abstract: Tris (chloropropyl)phosphate (TCPP) is a flame retardant currently used in upholstered furniture. This study provides the results of a follow up of TCPP concentrations in indoor air and at the surface of indoor materials in two offices after introduction of fireproof upholstered furniture (cushions made of PU foam containing TCPP). An emission cell coupled to solid-phase microextraction sampling was used as measurement means for direct measurement of gaseous TCPP concentration at the surface of the source material. Indoor TCPP concentrations reached high levels from 400 to 880 ng m −3 in correlation with gaseous concentrations measured at the surface of source materials (cushions) ranging from 5.5 to 17.7 μg m −3 . The changes in these concentrations showed no decline over more than 220 days and were mainly explained by temperature influence on emission. By applying the Clausius-Clapeyron equation, it was shown that the emission is close to vaporization of pure liquid TCPP. A model taking into account only the processes of emission/diffusion of compound in air and its removal by ventilation provided an acceptable prediction. Exposure by inhalation of occupants to TCPP in two offices were assessed to be 2933 ng.day −1 (with median level) and 4692 ng.day −1 (with maximum level). Highlights: On-site measurements of TCPP at the material surface in offices using a new method. Description of emission-concentration relationship in real indoor conditions. No decline in TCPP concentrations and emissions over more than 220 days. Changes in emission of source material mainly explained by temperature variation. A model giving an acceptable prediction of the mean levels of TCPP in indoor air.